Photocatalysts New Perspectives - Awwad, Nasser S.; Saeed Alarfaji, Saleh; Alomary, Ahmed (IntechOpen, 2023)
This book includes fourteen chapters on photocatalysis. It provides a thorough overview of the latest research on photocatalysts and examines recent trends in the field. Chapters address such topics as metal-organic frameworks, semiconductors, self-cleaning coatings and surfaces, the use of "green" agents to fabricate materials, fabrication of advanced nanocomposites for the production of hydrogen, bifunctional catalysts for metal-air batteries, and much more.